Personal dispositions as predictors of student nurses' prejudice, stereotyping, and discrimination against human immunodeficiency virus-infected persons in Osun State, Nigeria - Mudiaga Eugene Akpotor; Ezekiel Olasunkanmi Ajao; Margaret Ihunanya Okwuikpo; Tabitha Amere Leslie (Kashan University of Medical Sciences, 2020)
Background: Human immunodeficiency virus (HIV)/AIDS is a disease that is stigmatized as a result of its origin and outcome. HIV stigma may occur in the form of prejudice, stereotyping, and discrimination, collectively called HIV stigma mechanism. While studies have shown that student nurses are among persons who stigmatize, little is known about the role of their personal dispositions in the stigma process. Objective: This study aimed to examine the role of personal dispositions on their HIV stigma mechanism against HIV-infected persons. Methods: We employed a cross-sectional descriptive design involving 395 students across Osun State, Nigeria, using a modified Health Care Provider HIV/AIDS Stigma Scale instrument. Four personal dispositions (age, study level, HIV knowledge, and perception) serving as the independent variable, were of interest as well as the HIV stigma mechanism (prejudice, stereotyping, and discrimination) serving as the dependent variable in this study. Data were analyzed using mean and multiple linear regression analysis. Results: The mean scores of the categorical variables of knowledge about AIDS and perception of HIV-infected persons, measured on scales of 0-9 and 0-15, revealed moderate knowledge about HIV (5.90 ± 1.26) and negative perception (10.61 ± 2.47). For the dependent variables, the mean scores were 17.97 ± 4.07 for prejudice, 13.84 ± 3.34 for stereotyping, and 10.47 ± 3.22 for discrimination, which indicated that student nurses stigmatized HIV-infected patients. However, the core finding of this study revealed that, of all the predictors of HIV stigma mechanism, perception was the most significant. Conclusions: Personal dispositions are contributory factors to the enactment of HIV stigma mechanism. Future planning for intervention studies to reduce HIV stigma among health profession students should take cognizance of this.